2004
DOI: 10.1097/01.blo.0000136832.94824.91
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Gelatinases in Septic Arthritis of Native and Replaced Knees

Abstract: We hypothesized that more gelatinases appear in effusions of septic arthritis than aseptic arthritis. This study examined the laboratory variables of inflammation and the levels of gelatinase A and B (matrix metalloproteinases-2 and -9) in 75 effusions from the knees of 37 patients with inflammatory arthritis and compared them with effusions of septic and aseptic arthritis. Gelatin zymography revealed that the levels of the latent matrix metalloproteinase-9 were higher in 24 effusions of septic arthritis than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20]. Chu et al also showed by gelatin zymography that levels of latent MMP-9 and activated MMP-2 and MMP-9 were higher in effusions of septic arthritis than in effusions of aseptic arthritis [4]. Chu et al also showed by gelatin zymography that levels of latent MMP-9 and activated MMP-2 and MMP-9 were higher in effusions of septic arthritis than in effusions of aseptic arthritis [4].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20]. Chu et al also showed by gelatin zymography that levels of latent MMP-9 and activated MMP-2 and MMP-9 were higher in effusions of septic arthritis than in effusions of aseptic arthritis [4]. Chu et al also showed by gelatin zymography that levels of latent MMP-9 and activated MMP-2 and MMP-9 were higher in effusions of septic arthritis than in effusions of aseptic arthritis [4].…”
Section: Discussionsupporting
confidence: 93%
“…These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20]. These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the levels of latent and activated MMP-2 in all NSAIDs treated media at 24 h were unaltered in all tissue cultures (Figs. [3][4][5]. Significantly suppressive effects almost appeared from day 2, and persisted through to day 4; however, the decreases of proMMP-2 in celecoxib-treated meniscal cultures and activated MMP-2 in celecoxib-treated chondral cultures could not exhibit significant differences.…”
Section: Cytotoxicity Of Nsaids On the Cell Viability Of Tissue Culturesmentioning
confidence: 98%
“…Gelatinases (type IV collagenases) can be divided into gelatinase-A (MMP-2) and gelatinase-B (MMP-9) and their expressions increase in pathologic chondral, meniscal and synovial lesions of OA, which is likewise believed to play an important role in OA pathophysiology [2]. In fact, increased expression of gelatinases in arthritic effusions easily reflected the inflammatory condition of joints [3][4][5][6], and nonsteroidal antiinflammatory drugs (NSAIDs) may down-regulate the MMPs in synovial fluids of gouty arthritis [3]. Recently, the vital contribution of inflammation in cartilage destruction has been pointed out [7,8] and synovial inflammation has been implicated as a central component of OA pathogenesis [1].…”
Section: Introductionmentioning
confidence: 98%